Rancang Bangun Website Profil Dan Layanan Administrasi UKM Olahraga Politeknik Negeri Samarinda Berbasis Laravel - Fayad Zabihulloh; Noor Alam Hadiwijaya; Anton Topadang (Prodi Teknik Informatika Universitas Pasir Pengaraian, 2026)
The development of the Sports Student Activity Unit (UKM Olahraga) profile and administrative service website at the Samarinda State Polytechnic aims to provide a centralized web-based platform for organizational information and service management. The system enables students to access UKM profiles, sports divisions, activity schedules, news, galleries, member registration, and inventory loan services online. The system was developed using Laravel 11 as the backend, Filament v4 as the administration panel, Bootstrap 5 for the user interface, and MySQL as the database. The development method applied is the Web Development Life Cycle (WDLC), covering feasibility, analysis, design, coding, testing, deployment, and maintenance. The implemented features include UKM profile management, sports divisions and branches, activity and training schedules, news, galleries, new member registration, inventory borrowing, and an administration panel. Black Box Testing on 15 admin and user scenarios showed that all scenarios were successful, resulting in a 100% functional success rate. User Acceptance Testing (UAT) with UKM administrators on information access, content management, registration, borrowing, and ease of use indicators showed that the system was in accordance with organizational needs. Therefore, the website can support faster, more structured, and better documented management of UKM data and information dissemination.